Pelestarian Bahasa Rejang Sebagai Upaya Pengenalan Identitas Nasional Pada Siswa SDN 49 Bengkulu Tengah - Otopia, Yopita Sari; Syarkati, Syarkati (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to describe efforts to preserve the Rejang language as part of introducing national identity to students at SDN 49 Bengkulu Tengah. Regional languages are an important part of the nation's cultural heritage and play a strategic role in shaping national identity. This research is motivated by the declining use of the Rejang language among the younger generation, highlighting the need for concrete steps in its preservation through educational institutions.The study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The subjects of the research included the principal, teachers, and students. Data analysis was conducted through three stages: data reduction, data presentation, and drawing conclusions.The results of the study indicate that the preservation of the Rejang language at SDN 49 Bengkulu Tengah is carried out through local content learning, extracurricular activities, and integration into school programs. Teachers actively introduce vocabulary and simple conversations in the Rejang language. Challenges include the lack of learning media and low student interest in using regional languages. However, support from the school and community involvement are driving factors in the sustainability of this preservation program.This study concludes that schools play an important role in preserving regional languages as part of strengthening national identity. Synergy among schools, families, and communities is needed to maintain the existence of the Rejang language as a valuable cultural heritage.